Biofiltration of methane. (November 2018) - La, Helen; Hettiaratchi, J. Patrick A.; Achari, Gopal; Dunfield, Peter F.
Graphical abstract: Highlights: Critical review of methane biofiltration studies performed to date. Long-term performance monitoring should consider methanotroph community dynamics. Nitrogen metabolism influences methanotroph community and system performance. Methane biofiltration requires low energy input and inexpensive packing medium. Opportunity to displace fossil fuels by harvesting biomass for biocarbon. Abstract: The on-going annual increase in global methane (CH4 ) emissions can be largely attributed to anthropogenic activities. However, as more than half of these emissions are diffuse and possess a concentration less than 3% (v/v), physical-chemical treatments are inefficient as an abatement technology. In this regard, biotechnologies, such as biofiltration using methane-oxidizing bacteria, or methanotrophs, are a cost-effective and efficient means of combating diffuse CH4 emissions. In this review, a number of abiotic factors including temperature, pH, water content, packing material, empty-bed residence time, inlet gas flow rate, CH4 concentration, as well biotic factors, such as biomass development, are reviewed based on empirical findings on CH4 biofiltration studies that have been performed in the last decades.